Complement Activation-Related Pathophysiological Changes in Anesthetized Rats: Activator-Dependent Variations of Symptoms and Mediators of Pseudoallergy - László Dézsi; Tamás Mészáros; Erik Őrfi; Tamás G. Fülöp; Mark Hennies; László Rosivall; Péter Hamar; János Szebeni; Gábor Szénási (Molecules, 2019)
Complement (C) activation can underlie the infusion reactions to liposomes and other nanoparticle-based medicines, a hypersensitivity syndrome that can be partially reproduced in animal models. However, the sensitivities and manifestations substantially differ in different species, and C activation may not be the only cause of pathophysiological changes. In order to map the species variation of C-dependent and -independent pseudoallergy (CARPA/CIPA), here we used known C activators and C activator liposomes to compare their acute hemodynamic, hematological, and biochemical effects in rats. These C activators were cobra venom factor (CVF), zymosan, AmBisome (at 2 doses), its amphotericin B-free vehicle (AmBisombo), and a PEGylated cholesterol-containing liposome (PEG-2000-chol), all having different powers to activate C in rat blood. The pathophysiological endpoints measured were blood pressure, leukocyte and platelet counts, and plasma thromboxane B2, while C activation was assessed by C3 consumption using the Pan-Specific C3 assay. The results showed strong linear correlation between C activation and systemic hypotension, pointing to a causal role of C activation in the hemodynamic changes. The observed thrombocytopenia and leukopenia followed by leukocytosis also correlated with C3 conversion in case of C activators, but not necessarily with C activation by liposomes. These findings are consistent with the double hit hypothesis of hypersensitivity reactions (HSRs), inasmuch as strong C activation can fully account for all symptoms of HSRs, but in case of no-, or weak C activators, the pathophysiological response, if any, is likely to involve other activation pathways.